Correlation between dental caries severity and oral health knowledge in children aged 9-12 years in the agroindustrial area: an analytical observational study - Effendi, Fitria Yolanda Mellinia; Handayani, Ari Tri Wanodyo; Prihatiningrum, Berlian (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2024)
Introduction: Dental caries is a disease of hard tooth tissues that is often found in children, particularly those aged 9–12 years at the elementary school level. According to Riskesdas 2018, around 57.6% of Indonesia's population experiences dental and oral health problems, with a high prevalence of caries in school-age children. This condition is exacerbated by limited awareness of the importance of oral hygiene, leading to neglectful behaviors. This study aims to analyze the correlation between the severity of dental caries and oral health knowledge in children aged 9-12 years in the agro-industrial area. Methods: This research used an analytical observational design with a cross-sectional approach and included a total sample of 35 students selected using  a total sampling method. Data was collected through direct observation of oral cavity conditions and a self-developed questionnaire with questions about dental and oral health. Results: The sample included 14 male students and 21 female students, with the highest number of participants recorded in fifth-grade, totalling sixteen. The severity of dental caries, assessed using the CSI (Caries Severity Index), showed that the most frequent score was in the moderate category, with 31 cases across all grades. Knowledge of dental and oral health, measured using a questionnaire, showed that the most frequent score was in the good category, with 27 students across all grades. The Spearman correlation test showed no statistically significant relationship between dental caries severity and oral health knowledge in children aged 9-12 years, with a p-value of 0.180. Conclusion: There is no significant correlation found between dental caries severity and oral health knowledge in children aged 9-12 years in the agroindustrial area. Korelasi keparahan karies gigi dengan pengetahuan kesehatan gigi dan mulut pada anak usia 9-12 tahun di kawasan agroindustri: studi observasional analitik Pendahuluan: Karies gigi merupakan penyakit pada jaringan keras gigi yang banyak ditemukan pada anak-anak, terutama pada tingkat sekolah dasar usia 9-12 tahun. Menurut Riskesdas 2018, sekitar 57,6% penduduk Indonesia mengalami masalah kesehatan gigi dan mulut, dengan prevalensi karies yang tinggi pada anak-anak usia sekolah. Kondisi ini diperparah dengan kurangnya pengetahuan mengenai pentingnya perawatan gigi dan mulut, yang dapat menyebabkan sikap abai terhadap kebersihan gigi. Penelitian ini bertujuan untuk menganalisis korelasi  keparahan karies gigi dengan pengetahuan kesehatan gigi dan mulut pada anak usia 9-12 tahun yang berada di kawasan agroindustri. Metode: Jenis penelitian desain observasional analitik dengan pendekatan potong lintang (cross-sectional) dan melibatkan total sampel sebanyak 55 siswa, dengan metode total sampling. Data dikumpulkan melalui observasi langsung kondisi rongga mulut dan pengisian kuesioner dengan pertanyaan tentang kesehatan gigi dan mulut yang di kembangkan sendiri. Hasil: Terdapat 14 siswa laki-laki dan 21 siswa perempuan. Jumlah subjek terbanyak pada kasus kelas V dengan jumlah 16 siswa. Tingkat keparahan karies gigi dengan menggunakan CSI (Caries Severity Index) memiliki skor terbanyak adalah kriteria sedang sebanyak 31 pada semua kelas, pengetahuan kesehatan gigi dan mulut dengan menggunakan kuesioner memiliki skor terbanyak adalah kriteria baik dengan jumlah sebanyak 27 pada semua kelas. Hasil uji korelasi Spearman menunjukkan tidak terdapat korelasi yang signifikan antara keparahan karies gigi dan pengetahuan kesehatan gigi dan mulut pada anak usia 9-12 tahun, dengan p-value sebesar 0,180. Simpulan: Tidak terdapat korelasi keparahan karies gigi dengan pengetahuan kesehatan gigi dan mulut pada anak usia 9-12 tahun di kawasan agroindustri.